The Irish Statute Book : a constraint on the functioning of a true democracy - Hunt, Brian (Trinity College (Dublin, Ireland). School of Law, 2006)
Comprised of approximately 3,000 Acts enacted since the foundation of the State and a further 500 pre-1922 Acts, the Irish Statute Book has not been subjected to a detailed examination as to its form and present condition. One conclusion of this thesis is that the system of effecting legislative change is such that it mitigates to a considerable degree against the accessibility of the statute book. The approach for many years has been to heap one Act on top of the other with minimal effort at integration. The fruits of this approach have been a statute book whose characteristics are more sedimentary than ordered. It is unsurprising therefore that the need for a coherent statute book has greatly increased as a result of a combination of the system of effecting legislative change along with the inadequate arrangements for publication.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin